Integrating a gender perspective into transparency and accountability initiatives: three case studies. Issue 3 (2nd September 2017) - Powell, Alice
ABSTRACT: Natural resource wealth is not shared equally by all. While elites may capture the profits disproportionately in many contexts, marginalised social groups – including women – are less likely to experience the benefits of extraction, and are affected differently by virtue of their gendered roles in the economy and society. Women also tend to be less able to participate in decision-making forums relating to extractive questions. International transparency and accountability initiatives have been seeking to improve the management of natural resources through promoting citizen involvement and information disclosure in the extractive sector. Recently, some are also trying to incorporate gender issues into their work to ensure that women's experiences and voices are not excluded from the transparency movement. This article draws on evidence from transparency and accountability initiatives to show how they have tried to do this, in a field which has long been perceived as gender-neutral. It highlights some of the key challenges faced by these initiatives, as well as lessons they have learned in their work.